Surgical and Non-surgical Treatments in Pleural Empyema - Sami DENİZ; Nimet AKSEL; Özer ÖZDEMİR; Görkem VAYISOĞLU ŞAHİN; Ezgi ÇİMEN ÇELİK; Mutlu Onur GÜÇSAV; Filiz GÜLDAVAL; Ahmet Emin ERBAYCU; Ahmet ÜÇVET (Bezmiâlem Science)
Objective: Increasing number of patients are developing complicated pleural infection. We aimed at revealing the differences of treatment modalities performed in patients with empyema. Methods: Patients those had been diagnosed and treated for empyema were assessed in a retrospective design. For the definitive diagnosis of empyema, thoracentesis was made. We categorized the patients in two groups as therapeutic drainage (group 1) and open surgery (group 2). Results: A total of 360 patients, 57 of whom were women, were included. Tube drainage was applied to the patients in group 1, and therapeutic thoracentesis was applied to those not suitable for drainage. Patients who did not provide adequate drainage due to loculation were deloculated with fibrinolytic agent or video-assisted thoracoscopic surgery. In patients with advanced empyema with multiloculation and remarkable pleural thickening, which constituted group 2, decortication was performed by thoracotomy. Thoracoplasty was added in those who had insufficient lung volume. There were 292 (81.2%) patients in group-1 and 68 (18.8%) patients in group 2. In comparison of two groups, a significant difference was detected for lactate dehydrogenase (p<0.001) in pleural fluid and leukocyte count (p=0.05), hemoglobin (p=0.01), albumin (p=0.002), urea (p=0.3), and creatinine (p=0.21) levels in blood. The treatment results revealed no significant difference between three groups (recovered, sequelae changes, death), except for blood neutrophil count and antibiotic duration. Conclusion: Medical treatment plus therapeutic drainage therapy may be chosen as first treatment instead of open surgery in empyema.